Effects of Using Phenomenon-Based Learning along with CAMPER Critical Questions on Critical Reading Ability and Critical Thinking Ability of Eighth Grade Students - Saisaard, Siraphop; Satjapiboon, Suppawan (An Online Journal of Education, 2025)
The objectives of this research were as follows: 1) to compare the critical reading ability and critical thinking ability of eighth-grade students before and after using phenomenon-based learning along with CAMPER critical questions, and 2) to compare the critical reading ability and critical thinking ability of eighth-grade students who received phenomenon-based learning along with CAMPER critical questions, against a criterion of 70%. The sample for this research consisted of 35 eighth-grade students from Suratpittaya School, selected through cluster sampling. The research instruments were: 1) lesson plans based on phenomenon-based learning along with CAMPER critical questions. 2) the critical reading ability test. 3) the critical thinking ability test. The statistical methods used in the research were mean, standard deviation, Hotelling’s T2 and one sample t-test. The results revealed the following: 1) Students who received phenomenon-based learning along with CAMPER critical questions showed a significantly higher critical reading ability and critical thinking ability after learning compared to before, at the .05 significance level, and 2) Students who received phenomenon-based learning along with CAMPER critical questions showed a significantly higher critical reading ability and critical thinking ability after learning compared to a criterion of 70%, at the .05 significance level.